2020
DOI: 10.14202/vetworld.2020.2150-2155
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant strains of Mycobacterium complex species in Egyptian farm animals, veterinarians, and farm and abattoir workers

Abstract: Background and Aim: Mycobacterium tuberculosis complex (MTBC) is a group of mycobacteria that are important human pathogens. Mycobacterium tuberculosis and Mycobacterium bovis cause serious chronic life-threatening disease and also significant economic losses in both production and remedication. Recently, emergence of multidrug-resistant tuberculosis (MDR-TB) complex has generated global recognition of the need for rapid and sensitive diagnosis and development of new treatments. The current study illustrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Others have reported higher infection rates, ranging from 4.35% to 18.7% [ 20 - 22 ]. In this study, microscopic examination yielded results similar to those reported elsewhere [ 4 ], with rates of 2.56% in raw cow’s milk and 51.59% in lymph nodes. Microscopic examination of lymph nodes collected from tuberculin-positive animals by Z-N stain revealed M. bovis in 52/108 samples (48.1%), higher than the prior report, citing 21.43% [ 23 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Others have reported higher infection rates, ranging from 4.35% to 18.7% [ 20 - 22 ]. In this study, microscopic examination yielded results similar to those reported elsewhere [ 4 ], with rates of 2.56% in raw cow’s milk and 51.59% in lymph nodes. Microscopic examination of lymph nodes collected from tuberculin-positive animals by Z-N stain revealed M. bovis in 52/108 samples (48.1%), higher than the prior report, citing 21.43% [ 23 ].…”
Section: Resultssupporting
confidence: 89%
“…In humans, it causes approximately 3 million deaths every year. It affects domestic and wild animals and is characterized by progressive development of tubercles or characteristic granulomatous lesions in lung tissue, lymph nodes, or other organs [ 4 ]. Diagnosis of TB requires measuring either a humoral or cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…From Table 1, it appears that results of direct smear were less than those reported by Sohair and Riad (2002) who detected 69% positive cases but higher than 46.88% and 48.04% reported by Silva et al (2018) and Abdelsadek et al (2020). Regarding culture, the obtained results in Table 1 are consistent with those reported by Silva et al (2018) and Hamed et al (2021) who detected M. bovis in 68.75% and 64.9% of tested samples, respectively, but were less than 80%, 71.4% and 85% reported by Nasr et al (2016), Mohammed (2017) and Borham et al (2021), respectively.…”
Section: Discussionmentioning
confidence: 61%
“…As per CPCSEA guidelines (Pandey and Sharma 2011), a study involving clinical and postmortem samples does not require the approval of the Institute Animal Ethics Committee. Those guidelines were followed in the study (Abdelsadek et al 2020) which was conducted on postmortem samples. However, all owners of slaughtered cattle have signed a consent form.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Furthermore, they confirmed the absence of genetic relationship between human M. bovis strains or between human and bovine strains. Recently, Abdelsadek et al in Egypt tested 135 MBTC isolates obtained from both infected cattle and veterinarians or workers in contact with these animals [ 158 ]. The study reported high resistance for both PZA and INH of 78.5% and 59.3%, respectively.…”
Section: Multidrug and Extensively Drug-resistant Tb And Btbmentioning
confidence: 99%